If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + x + -1(cos(2x)) = 0 Remove parenthesis around (2x) 2 + x + -1(cos * 2x) = 0 Reorder the terms for easier multiplication: 2 + x + -1(2cos * x) = 0 Multiply cos * x 2 + x + -1(2cosx) = 0 Remove parenthesis around (2cosx) 2 + x + -1 * 2cosx = 0 Multiply -1 * 2 2 + x + -2cosx = 0 Reorder the terms: 2 + -2cosx + x = 0 Solving 2 + -2cosx + x = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2cosx + -2 + x = 0 + -2 Reorder the terms: 2 + -2 + -2cosx + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2cosx + x = 0 + -2 -2cosx + x = 0 + -2 Combine like terms: 0 + -2 = -2 -2cosx + x = -2 Add '-1x' to each side of the equation. -2cosx + x + -1x = -2 + -1x Combine like terms: x + -1x = 0 -2cosx + 0 = -2 + -1x -2cosx = -2 + -1x Divide each side by '-2osx'. c = o-1s-1x-1 + 0.5o-1s-1 Simplifying c = o-1s-1x-1 + 0.5o-1s-1 Reorder the terms: c = 0.5o-1s-1 + o-1s-1x-1
| -cos(2x)+x+2=0 | | n=23-n-35-29 | | ×/3-3×/2=1/6-× | | 4x-(3x+40000)=0 | | 4x-3x-40000=0 | | n+23-n-35=29 | | (4x+3x)-40000=0 | | n+23-n=35-29 | | 10x+18y+5+8x-10y-3= | | 4x+3x-40000=0 | | n+23=n-35-29 | | n=10(7+11)-180 | | 2(n)+5=45-20 | | An=An-3 | | n+15=35-n-25 | | 4k-5k^2=0 | | 4a+42=90 | | 2(x-5)3x=2 | | x^2-40x-150=0 | | (x-5)(2x-4)= | | an=33n | | f(7a)=7a+7 | | (12+z+-3y)-y+2z=4 | | 43.44= | | 3/2x=3.5 | | (6j)/(7-6j) | | 2x+1-3x-7= | | 8y/4z | | -36y^2=100 | | kx^2=4x-4 | | 4x+(2x-7)=0 | | Dy+Jt=R |